Cultural ideologies and outgroup action tendencies of left-behind children of Overseas Filipino Workers - Allan B. I. Bernardo; Kimberly Kaye C. Mata; Melissa R. Garabiles (Cogent Psychology)
At least 1.5 M Filipino children are left behind by parents who are Overseas Filipino Workers (OFWs). We explore whether left-behind children develop more positive intercultural beliefs and behavioral intentions compared to their peers, as they are made aware of foreign cultures through parents’ intercultural experiences. We surveyed 949 high school students, 103 of whom are left-behind children; the questionnaire included cultural ideologies and outgroup action tendencies scales. Controlling national identification measures as covariates, the results show that the left-behind children have more negative outgroup action tendencies and weaker approach tendencies towards people from other cultures. The intercultural experiences of OFW parents are not associated with more positive intercultural beliefs, suggesting the left-behind children might be constructing their intercultural knowledge considering some negative information about OFW’s experiences.